Evaluation as an Element of the Management of Non-Financial Assets of Public Sector Institutions - Olena Tsiatkovska (Облік і фінанси, 2023)
Evaluation plays a vital role in the management of non-financial assets in public sector institutions, which explains the significant interest of researchers in finding ways to improve it, analyzing the advantages and disadvantages of different approaches to evaluation, and studying the evaluation practice according to International Evaluation Standards. The purpose of the article is to reveal the features of evaluation as an element of management of non-financial assets of state institutions, as well as to analyze the features and approaches to assessing non-financial assets depending on their types and conditions of use. The structure of national and international evaluation standards was revealed. In the wartime and the post-war recovery of Ukraine's economy, it is advisable to rely on the results of evaluation conducted by the International Evaluation Standards, which are fundamental when making investment decisions, preparing financial statements, and ensuring regulatory lending requirements. Thus, the European integration of Ukraine is only possible with the implementation of the International Evaluation Standards, which can be implemented in several ways: full or partial application, as well as the development of national evaluation standards based on international ones. Valuation is not only one of the elements of the accounting method; valuation is an independent system consisting of such elements as the object and subject of evaluation, the subject matter of evaluation, and the subjective and objective side of evaluation. The article discloses certain aspects of the evaluation of non-financial assets of state institutions. Special attention is focused on justifying the expediency of choosing one or another approach to evaluation. It was determined that applying the cost approach to the evaluation of non-created non-financial assets is the most appropriate, which, however, does not exclude the possibility of combining it with other approaches in practice. Implementing International Valuation Standards in Ukrainian legislation will avoid opaque methodology and manifestations of subjectivism in selecting approaches to the valuation of non-financial assets of state institutions.